Effect of body weight on static and dynamic posturography - Afaf Emara (The Egyptian Journal of Otolaryngology, 2020)
Abstract Background Postural balance is important to allow us to maintain the daily life. Poor postural response and reduced motor activity were shown to be most prominent among obese persons than in non-obese. It is found that obese elderly groups show a high prevalence of fall and supposed that adipose tissue distribution may be considered as a major factor to balance problems. In this research, we studied computerized dynamic posturography (CDP) static and dynamic tests among healthy adults according to their BMI classification (underweight/normal weight/overweight/obese). Results We found a significant difference between studied groups among the different scores recorded from sensory organization test and rhythmic weight shift test, which means the presence of an effect of increased body mass index on the different sensory systems required to maintain balance control and the motor strategy used to maintain balance. In obese elderly subjects, there was increased reliance on vestibular system to maintaining balance. With increasing BMI, there was decrease in visual dependence in maintaining balance. Conclusions Increased body weight affects the balance function of the normal individual. Computerized dynamic posturography is a good test to study static and dynamic status among obese subjects. So we found a positive relation between aging, BMI, and postural control.